Mortality in combined pulmonary fibrosis and emphysema patients is determined by the sum of pulmonary fibrosis and emphysema. Issue 3 (23rd August 2021) - Zhao, An; Gudmundsson, Eyjolfur; Mogulkoc, Nesrin; Jones, Mark G.; van Moorsel, Coline; Corte, Tamera J.; Romei, Chiara; Savas, Recep; Brereton, Christopher J.; van Es, Hendrik W.; Jo, Helen; De Liperi, Annalisa; et al.
Emphysema is one of the most common pulmonary comorbidities of idiopathic pulmonary fibrosis (IPF), presenting in about one-third of IPF patients [1]. The term combined pulmonary fibrosis and emphysema (CPFE) has been used to describe a potential phenotype characterised by the coexistence of upper lobe-predominant emphysema, lower lobe-predominant fibrosis and relative preservation of lung volumes (forced vital capacity; FVC) in the context of a disproportionately reduced gas transfer (diffusing capacity of the lung for carbon monoxide; D LCO ) [1–3]. With regard to patient survival, it remains unclear whether mortality in patients with CPFE reflects the cumulative effects of two disease processes (emphysema and fibrosis), or whether CPFE represents a distinct disease phenotype where outcome is worse than the sum of disease parts (emphysema and fibrosis). In patients with combined pulmonary fibrosis and emphysema, emphysema and fibrosis do not have a synergistic effect that results in worsened survival when compared to IPF patients without emphysema https://bit.ly/35EJMo6